2020
DOI: 10.1074/jbc.ra119.011270
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of protein phosphatase 2A (PP2A) complexity reveals cellular functions and dephosphorylation motifs of the PP2A/B′δ holoenzyme

Abstract: Protein phosphatase 2A (PP2A) is a large enzyme family responsible for most cellular Ser/Thr dephosphorylation events. PP2A substrate specificity, localization, and regulation by second messengers rely on more than a dozen regulatory subunits (including B/R2, B′/R5, and B″/R3), which form the PP2A heterotrimeric holoenzyme by associating with a dimer comprising scaffolding (A) and catalytic (C) subunits. Because of partial redundancy and high endogenous expression of PP2A holoenzymes, traditional approaches of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…A major hurdle to determining how the E420K mutation alters the biological functions of PPP2R5D is that only a few studies have explored the "normal" action(s) of PPP2R5D at a cellular level (31,32). Therefore, we chose a global unbiased approach, employing TMT labeling for relative and absolute quantitation with LC-MS 3 , to obtain proteomic (Fig.…”
Section: Quantitative Changes In the Proteome And Phosphoproteome In Ppp2r5d E420k Variant Cellsmentioning
confidence: 99%
“…A major hurdle to determining how the E420K mutation alters the biological functions of PPP2R5D is that only a few studies have explored the "normal" action(s) of PPP2R5D at a cellular level (31,32). Therefore, we chose a global unbiased approach, employing TMT labeling for relative and absolute quantitation with LC-MS 3 , to obtain proteomic (Fig.…”
Section: Quantitative Changes In the Proteome And Phosphoproteome In Ppp2r5d E420k Variant Cellsmentioning
confidence: 99%
“…Of these 232 phosphopeptides, 168 peptides increased and 64 decreased in abundance relative to matched untreated controls reflecting increase or decrease in phosphorylation status, respectively (Dataset S1). Comparison with available phosphoproteomic datasets derived from studies of GPCR/cAMP activation revealed extensive overlap (65/218 sites = 30%) [7][8][9][10][11][12][13][14] . Of particular significance, we confirmed 1/3 of GPCR/cAMP target phosphosites previously reported in the same cell type, HEK293 cells 14 .…”
Section: Resultsmentioning
confidence: 99%
“…In this subset, 20 of these 22 peptides (>90%) had the motif (p < 1.2x10 -4 by Fisher's exact test). Two protein phosphatases, PP1A and PP2A, are known to modify prolinedirected sequences 11,24 . Hence, we searched the mass spectrometry data and found a peptide corresponding to a known regulatory site within the PP2A-B56δ subunit, S573.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…In this subset, 20 of these 22 peptides (>90%) had the motif ( p < 1.2×10 −4 by Fisher’s exact test). Two protein phosphatases, PP1A and PP2A, are known to modify proline-directed sequences 11,24 . Hence, we searched the mass spectrometry data and found a peptide corresponding to a known regulatory site within the PP2A-B56δ subunit, S573.…”
Section: Resultsmentioning
confidence: 99%